2022
DOI: 10.2147/idr.s371431
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Extended-Spectrum β-Lactamase and Carbapenemase Producers of Gram-Negative Bacteria, and Methicillin-Resistant Staphylococcus aureus in Isolates from Diabetic Foot Ulcer Patients in Ethiopia

Abstract: Background Infectious diabetic foot ulcers (IDFU) are a widespread health issue that affects people all over the world. IDFU, like other medical disorders, can have negative implications if drug resistance develops. Clinicians will be able to choose the optimal antibiotics to treat impacted patients based on the antibiotic susceptibility pattern of bacterial strains. In this project, we attempted to evaluate the levels of extended-spectrum beta-lactamase (ESBL), carbapenemase, and MRSA in patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…exhibited susceptibility to linezolid, chloramphenicol, and rifampicin [22]. Another study conducted in 2022, Woldeteklie et al found a high resistance in S. aureus to methicillin, with 81.3% (26/32) identified as MRSA, and 18.7% (6/32) were MSSA [23]. This study reported that 50% of the screened MRSA isolates were sensitive to amikacin and chloramphenicol.…”
Section: Antimicrobial Sensitivity Profilementioning
confidence: 69%
“…exhibited susceptibility to linezolid, chloramphenicol, and rifampicin [22]. Another study conducted in 2022, Woldeteklie et al found a high resistance in S. aureus to methicillin, with 81.3% (26/32) identified as MRSA, and 18.7% (6/32) were MSSA [23]. This study reported that 50% of the screened MRSA isolates were sensitive to amikacin and chloramphenicol.…”
Section: Antimicrobial Sensitivity Profilementioning
confidence: 69%